A Multiband Printed Slot Antenna Loaded with Trapezoidal Slots for WLAN and WiMax Applications - H.T. Ziboon (Engineering and Technology Journal, 2018)
In this paper, a multiband printed antenna has been proposed. The antenna structure is inspired from that of the classical multi-cavity magnetron resonator. The antenna structure is composed of a slot annular ring structure etched on the ground plane of a substrate. The outer circle of the annular ring is loaded with radially arranged small trapezoidal slots. While on the other side of the substrate, the antenna is fed with a 50-Ohm microstrip line. A parametric study has been conducted to explore the effect of the different antenna dimensions on its performance. The results show that the proposed antenna offers triple band resonant responses with considerable frequency ratios of f3/f2, and f2/f1. Measured results of the input reflection coefficient responses of a fabricated prototype are found to agree well with the theoretical findings. The antenna has an input reflection coefficient response enables it to serve the 2.4/5.2 GHz WLAN and the 3.5/4.5 GHz WiMax applications. Besides, the antenna offers reasonable radiation characteristic with acceptable values of the gain throughout the four resonant bands.